2005
DOI: 10.1111/j.1365-3083.2005.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Release of Intact and Cleaved Urokinase Receptor in Stimulated Whole‐Blood Cultures from Human Immunodeficiency Virus‐1‐Infected Patients

Abstract: The blood levels of the soluble forms of the urokinase receptor (suPAR) are increased in human immunodeficiency virus (HIV)-1-infected patients. This study investigated whether the release of urokinase-type plasminogen activator receptor (uPAR) in whole-blood cultures was affected by HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Hypothetically, if HIV‐1‐infection increases both expression [6, 24, 25] and shedding of uPAR(I–III) and thereby induces relatively reduced cellular uPAR(I–III) expression [26] and hence reduced uPAR(I–III) cleavage [22, 23], this could, together with a short half‐life of circulating suPAR(I) [14, 15, 27, 28], in part explain the modest increase in suPAR(I) in HIV‐1‐infected patients. We have previously shown that release of intact and cleaved uPAR in 24 h stimulated whole‐blood cultures from HIV‐1‐infected patients is reduced compared with healthy individuals [26]. This finding could indicate that circulating immune cells from HIV‐1‐infected patients have reduced uPAR expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothetically, if HIV‐1‐infection increases both expression [6, 24, 25] and shedding of uPAR(I–III) and thereby induces relatively reduced cellular uPAR(I–III) expression [26] and hence reduced uPAR(I–III) cleavage [22, 23], this could, together with a short half‐life of circulating suPAR(I) [14, 15, 27, 28], in part explain the modest increase in suPAR(I) in HIV‐1‐infected patients. We have previously shown that release of intact and cleaved uPAR in 24 h stimulated whole‐blood cultures from HIV‐1‐infected patients is reduced compared with healthy individuals [26]. This finding could indicate that circulating immune cells from HIV‐1‐infected patients have reduced uPAR expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether circulating immune cells from HIV‐1‐infected patients, e.g. have reduced uPAR expression [26] compared with immune cells residing in lymphoid tissues. Thus, further studies are required to interpret differences in the blood level of individual suPAR forms in patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In a wide population of acute medical patients, suPAR is strongly associated with disease severity and mortality, suggesting that suPAR could be used in the clinic as a prognostic indicator [ 24 ]. Several studies have indicated that serum suPAR levels correlate with the severity of infection and have reported a strong association with mortality in patients with malaria, tuberculosis, and human immunodeficiency virus (HIV) infection [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soluble urokinase plasminogen activator receptor is the soluble form of uPAR, a membrane-bound receptor that is expressed on immune and endothelial cells and involved in several cellular processes, including adhesion, differentiation, proliferation, and migration (Blasi & Carmeliet, 2002). Immune and proinflammatory conditions increase the expression and cleavage of uPAR (Dekkers, ten Hove, te Velde, van Deventer, & van Der Poll, 2000;Ostrowski et al, 2005). The resulting suPAR is a stable circulating molecule with intrinsic chemotactic properties (Resnati et al, 2002), and the level of suPAR is thought to reflect the overall immune activity of an individual (Desmedt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%